Treatment of PLGA Nanoparticles Ointment-Ethanol Extract of Archidendron pauciflorum in the Wound Healing in Diabetic Mice - Malini, Desak Made; Kuntana, Yasmi Purnamasari; Madihah, Madihah; Furqon, Wildanul; Hermawan, Wawan (Jurnal Biodjati, 2020)
Diabetic wounds lead to severe tissue damage and are diffi-cult to cure. Jengkol (Archidendron pauciflorum) is a plant commonly used by local Indonesian communities to treat diabetic wounds. The efficiency of herbal medicine still has a deficiency of its ability to reach the target organs, therefore nanotechnology is applied in the hope that all drug concentrations can reach the target organs successfully. This study aimed to evaluate the effectiveness of PLGA nanoparticle ointment-ethanol extract jengkol fruit peel (EEJFP) to accelerate the wound healing process in the skin of streptozotocin-induced diabetic mice. The research method used was experimental with a completely randomized design using six treatments and four replications. Diabe-tes was induced by intraperitoneal injection of streptozotocin 180 mg/ kg BW. Mice with a blood glucose level of â‰¥150 mg/dL were used for diabetic mice models. The incision wound created at the dorsolateral region of shaven skin at Â±1 cm2 using sterile scissors. The treatments given were vaseline for Control Negative (CN) and Control Positive (CP), Betadine ointment (PB), 10% EEJFP ointment (P1), 5% PLGA nanoparticle ointment-EEJFP (P2), and 2.5% PLGA nanoparticle ointment-EEJFP (P3). The results showed that the administration of PLGA nanoparticles ointment-EEJFP with a concentration of 5% PLGA nanoparticle ointment-EEJFP (P2) resulted in the shortest wound length on day 3, 7 and 14; narrower granulation tissue; a larger number of blood capillaries; and denser collagen fibers (Î± <0.05) compared to CP and PB treatments. The administration of PLGA nanoparticle ointment-EEJFP with a concentration of 5% was the most effective concentration in accelerating wound healing in the skin of diabetic mice.Â